India : modern architectures in history - Scriver, Peter; Srivastava, Amit (Modern architectures in history., 2015)
"India: Modern Architectures in History shows how the architecture of 'Modern India" reflected and embodied the dramatic shifts of Indian society and culture. Peter Scriver and Amit Srivastava explore how Indian architectural modernity began in the early twentieth century, as public works and patronage fostered new design practices that directly challenged the social order and values invested in the building traditions of the past. This is the first book to examine both colonial and postcolonial aspects in comparable depth, and the authors draw together a broad range of sources, including private papers, photographic collections and the extensive records of the Indian Public Works Department system"--Page 4 of cover.